O ESPAÇO DE MORAR E A ARQUITETURA MODERNISTA: REFLEXÕES A PARTIR DE IRATI – PR - Mendes, Gigliese Aparecida (2013)
The modernist architecture is strongly presented in the urban scenery of Irati-PR. Such movement arrived to this town from 1950`s, what indicates a certain temporal delay, considering that this movement was booming in 1920`s in large urban centers. The base of this research is the dialectic relationship between local and global scales, in order to show the ways that a globalized movement wields local influence, mixing to individuals` life and establishing a ‘glocal’ culture. The focus of this research is the modernist ‘living space’ in which are analyzed twelve single-familiy residences built from 1950’s to 1970’s, that was projected by Eduardo Posfaldo, a local professional that strongly presented lecorbusioan influence. In these are observed modernist architectonic elements, such as pans de verre, platibands and pilotis. The “living machine”, that was largely discussed in the modernist movement, has its space linked to practicality, and the beauty of its frontages is allied to the functionality of the interior rooms. Based on the analysis of these habitations, it is possible to establish that they follow a pattern in the distribution of the intern spaces, privileging the private spaces followed by the social ones. Furthermore, it was found singularities in the modernist architecture of Irati-Pr, such as the use of wood in frontage details, and the presence of integrated “professional spaces” in some cases.